Students' Mathematical Creative Thinking Ability in terms of Learning Styles and Gender in Problem Based Learning - Rizqi, Muhammad; Suyitno, Hardi; Dwijanto, Dwijanto (Universitas Negeri Semarang, 2021)
This researchaims to describe students' mathematical creative thinking abilities in terms of learning styles and gender.The method used is descriptive qualitative, data collection techniques in this study were carried out through direct activities at school. Data collection was carried out by means of tests of mathematical creative thinking skills, learning style questionnaires, interviews and documentation.The results of the research are (1) students 'mathematical creative thinking abilities in terms of visual and gender learning styles are more likely to fulfill authenticity and detail indicators, but what is unique is that only one subject can fulfill fluency and flexibility indicators, (2) students' mathematical creative thinking abilities in terms of style. Auditory learning and gender are more likely to meet the indicators of authenticity and detail, however, what is unique is that only one subject cannot meet the indicators of flexibility and fluency, and (3) students' mathematical creative thinking abilities in terms of kinesthetic learning styles and gender, there are only two students who tend to fulfill indicators of fluency, flexibility and detail and two students meet indicators of fluency and detail because they are able to solve problems in a very detailed and systematic manner,while the other two students only meet the authenticity indicator